Prevalence and associated factors for hepatitis B infection among pregnant women attending antenatal clinic at SOS Hospital in Mogadishu, Somalia - Hassan, Shafie Abdulkadir; Ahmed, Yousif Mousa Alobaid; Almugadam, Babiker Saad; Hassan, Yahye Sheikh Abdulle (Frontiers in Global Women's Health, 2024)
Background Hepatitis B virus (HBV) remains a leading cause of chronic hepatitis, maternal complications, and neonatal deaths in sub-Saharan Africa. Mother-to-child transmission is a major route of HBV transmission in endemic areas. This study aimed to determine the prevalence of hepatitis B infection and its associated factors among pregnant women attending Antenatal Care clinics at SOS Hospital in Mogadishu, Somalia. Methods The research followed a cross-sectional design, and the participants were chosen through systematic random sampling, including every fifth outpatient. Each participant provided a blood sample for standard testing, and their consent was obtained before conducting Hepatitis B screening using the ELISA method. Results In our study of 384 pregnant women, 43 individuals (11.2%) tested positive for HBsAg. Those with primary education had significantly lower odds of HBV infection (AOR = 0.1, 95% CI: 0.01-0.96, p = 0.046). Caesarian Section (AOR = 0.02, 95% CI: 0.004-0.0103, p = 0.001), blood transfusion (AOR = 11.6, 95% CI: 3.44-38.08, p = 0.001), previous dental procedures (AOR = 0.1, 95% CI: 0.04-0.38, p = 0.001), and unsafe injections in the past (AOR = 0.3, 95% CI: 0.09-0.91, p = 0.004) were identified as significant risk factors for hepatitis positivity. Conclusions The study found a higher prevalence of hepatitis B compared to previous studies. Factors such as blood transfusion, dental procedures, Caesarian Section, and unsafe injections were associated with hepatitis B infection. It is essential to raise awareness, promote preventive measures, and implement routine screening for pregnant women so as to stop the transmission of hepatitis B to their children.